CEREBRAL AMYLOID ANGIOPATHY-RELATED INFLAMMATION: A COMPLEX CASE. Issue 12 (15th November 2016) - Cousins, Oliver; Patel, Bhavini; Khan, Usman
Abstract : Introduction: Cerebral amyloid angiopathy-related inflammation (CAA-I) is a rare neurological condition with significant morbidity and mortality. Here we present a case of CAA-I that demonstrates its varied clinical course. Case: A 76-year-old woman presented with subacute headache. Further assessment revealed mild cognitive impairment and left quadrantanopia. Right hemisphere hyperdensity was observed on MRI FLAIR sequence suggesting inflammatory amyloid. Steroid treatment was commenced for probable CAA-I but was eventually discontinued due to severe side effects. Clinical improvement was noted and corroborated by re-imaging which demonstrated complete resolution of the inflammatory changes. Cognitive decline occurred again 8 months later. MRI showed right hemisphere hyperdensity with microbleeds on gradient echo, in keeping with a CAA-I relapse. She underwent brain biopsy which confirmed underlying CAA although no inflammatory cells were seen. Remarkably she subsequently improved clinically and radiologically without having undergone any medical treatment suggesting a spontaneous remission of her CAA-I. Discussion: Despite criteria for non-invasive diagnosis of CAA-I, using clinical features and radiology (Chung criteria), brain biopsy is still sometimes required to make the diagnosis. Successful treatment can be achieved, particularly with corticosteroids. Our case not only highlights how patients can relapse off of treatment but also that spontaneous remission is possible.